(3QSGdI GHf YQHi Edi GdaNQ GdQGRis - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfG GdMeO Edjc Gddg GdPi dG Edg EdG gh hbGd QShd Gddg Udi Gddg Ydjg hSde EPG GMH GMOce GNGg adjYdeg EjGg s
(3BNQgG (B:s
(3hcfJ GPcQ GdMdhI hTQhWgG hHCYdi efgG Ydi GdJQJjH Ef de jcf GdEjeGf JeJ GdQSGdI HYhf Gddg hMSf JhajbI s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3483(14)) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs